2019
DOI: 10.1007/s11325-019-01791-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of screening instruments for obstructive sleep apnea in morbidly obese patients referred to a sleep laboratory: a prospective cross-sectional study

Abstract: Purpose Obstructive sleep apnea (OSA) is very common occurrence among morbidly obese patients. Our main objectives were to validate the No-Apnea, a 2-item screening tool, in morbidly obese patients and compare its performance with three other instruments: STOP-Bang questionnaire, NoSAS score, and Epworth Sleepiness Scale (ESS). Methods A cross-sectional analysis of morbidly obese patients (body mass index [BMI] ≥ 35.0 kg/m 2 ) grouped into two independent samples: bariatric surgery patients (BS) and non-bariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…Importantly, when used for preoperative screening (i.e., identification of the highest‐risk individuals who warrant further testing with a sleep study), both STOP‐BANG and NO‐OSAS appeared to have a higher specificity (i.e., lower false‐positive rate) compared with No‐Apnea and the ESS, although confidence intervals (CI) slightly overlapped. This is consistent with a study by Duarte et al, which also found a lower specificity with No‐Apnea compared with STOP‐BANG when using cutoffs with comparable sensitivity (15). Moreover, our results validate the use of previously established cutoffs for the screening of moderate to severe OSA in a diverse bariatric surgery population: as in prior studies, STOP‐BANG ≥ 4, NO‐OSAS ≥ 3, and No‐Apnea ≥ 3 achieved a sensitivity > 80% while maintaining a similar specificity as in previous studies (50%‐60% for STOP‐BANG and NO‐OSAS vs. 30%‐40% for No‐Apnea) (3,15,17).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, when used for preoperative screening (i.e., identification of the highest‐risk individuals who warrant further testing with a sleep study), both STOP‐BANG and NO‐OSAS appeared to have a higher specificity (i.e., lower false‐positive rate) compared with No‐Apnea and the ESS, although confidence intervals (CI) slightly overlapped. This is consistent with a study by Duarte et al, which also found a lower specificity with No‐Apnea compared with STOP‐BANG when using cutoffs with comparable sensitivity (15). Moreover, our results validate the use of previously established cutoffs for the screening of moderate to severe OSA in a diverse bariatric surgery population: as in prior studies, STOP‐BANG ≥ 4, NO‐OSAS ≥ 3, and No‐Apnea ≥ 3 achieved a sensitivity > 80% while maintaining a similar specificity as in previous studies (50%‐60% for STOP‐BANG and NO‐OSAS vs. 30%‐40% for No‐Apnea) (3,15,17).…”
Section: Discussionsupporting
confidence: 92%
“…Several instruments have been developed over the years including the STOP-Bang questionnaire [6,7] and the NoSAS score [8]. The STOP-Bang questionnaire shows a high sensitivity and negative predictive value, and therefore is a suitable instrument to rule out patients at risk for OSA [9][10][11][12]. However, it has a low to moderate specificity and it is possible that this will yield a high false-positive rate.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire score ranges between 0 and 24. Higher total scores are related to more sleepiness [39].…”
Section: Questionnairesmentioning
confidence: 95%